Preclinical evaluation of injectable bone substitute materials. (8th November 2012) - Bongio, Matilde; van den Beucken, Jeroen J. J. P.; Leeuwenburgh, Sander C. G.; Jansen, John A.
Abstract: Injectable bone substitutes (IBSs) represent an attractive class of ready‐to‐use biomaterials, both ceramic‐ and polymer‐based, as they offer the potential benefit of minimally invasive surgery and optimal defect filling. Although in vitro assessments are the first step in the process of development, the safety and efficacy of an IBS strongly depend on validated preclinical research prior to clinical trials. However, the selection of a suitable preclinical model for performance evaluation of an IBS remains a challenge, as no gold standard exists to define the best animal model. In order to succeed in this attempt, we identified three stages of development, including (a) proof‐of‐principle, (b) predictive validity and (c) general scientific legitimacy, and the respective criteria that should be applied for such selection. The second part of this review provides an overview of commonly used animals for IBSs. Specifically, scientific papers published between January 1996 and March 2012 were retrieved that report the use of preclinical models for the evaluation of IBSs in situations requiring bone healing and bone augmentation. This review is meant not only to describe the currently available preclinical models for IBS application, but also to address critical considerations of such multi‐factorial evaluation models (including animal species, strain, age, anatomical site, defect size and type of bone), which can be indicative but in most cases edge away from the human reality. Consequently, the ultimate goal is to guide researchers toward a more careful and meaningful interpretation of the results of experiments using animal models and their clinical applications. Copyright © 2012 John Wiley & Sons, Ltd.